Pattern of all-causes and cause-specific mortality in an area with progressively declining malaria burden in Korogwe district, north-eastern Tanzania - Daniel P. Challe; Mathias L. Kamugisha; Bruno P. Mmbando; Filbert Francis; Mercy G. Chiduo; Celine I. Mandara; Samuel Gesase; Omari Abdul; Martha M. Lemnge; Deus S. Ishengoma (Malaria Journal, 2018)
Abstract Background Although death records are useful for planning and monitoring health interventions, such information is limited in most developing countries. Verbal autopsy (VA) interviews are alternatively used to determine causes of death in places without or with incomplete hospital records. This study was conducted to determine all causes and cause-specific mortality in Korogwe health and demographic surveillance system (HDSS) undertaken in Korogwe district, northeastern Tanzania. Methods The study was conducted from January 2006 to December 2012 in 14 villages under Korogwe HDSS. Vital events such as births, deaths and migrations were routinely updated quarterly. A standard VA questionnaire was administered to parents/close relatives of the deceased to determine cause of death. Results Overall, 1325 deaths of individuals with median age of 46 years were recorded in a population with 170,471.4 person years observed (PY). Crude mortality rate was 7.8 per 1000 PY (95% CI 7.2–8.4) and the highest rate was observed in infants (77.9 per 1000 PY; 95% CI 67.4–90.0). The overall mortality increased between 2006 and 2007, followed by a slight decline up to 2011, with the highest decrease observed in 2012. Causes of deaths were established in 942 (71.1%) deaths and malaria (198 deaths, 21.0%) was the leading cause of death in all age groups except adults (15–59 years). HIV/AIDS (17.6%, n = 365) was the leading cause of death in individuals aged 15–59 years followed by malaria (13.9%) and tuberculosis. Non-communicable diseases (NCDs) including stroke, hypertension, cancer, and cardiac failure caused majority of deaths in elderly (60 years and above) accounting for 37.1% (n = 348) of all deaths, although malaria was the single leading cause of death in this group (16.6%). Conclusion The study showed a significant decline of deaths in the Korogwe HDSS site and malaria was the main cause of death in all age groups (except adults, aged 15–59 years) while HIV/AIDS and NCDs were the main causes in adults and elderly, respectively. Further surveillance is required to monitor and document changes in cause-specific mortality as malaria transmission continues to decline in this and other parts of Tanzania.